SOLUBILITY ENHANCEMENT OF POOR WATER SOLUBLE DRUGS BY SOLID DISPERSION: A REVIEW - Mankar, SD; Rach, Punit R. (Journal of Drug Delivery and Therapeutics, 2018)
The solubility behavior of drugs remains one of the most exigent aspects in formulation development. With the advent of combinatorial chemistry and high throughput screening, the number of poorly water soluble compounds has dramatically increased. Among all the newly discovered chemical entities, about 40-45% drugs fail to reach market due to their poor water solubility. Because of solubility problem, bioavailability of drugs gets affected and hence solubility enhancement becomes necessary. Solid dispersions have attracted considerable interest as an efficient means of improving the dissolution rate and hence the bioavailability of drugs. Therefore, the application of this technique proves to be an important stratagem for pharmaceutical companies. However, the in - depth knowledge of the solid dispersion is desired for the scale up of formulation, from laboratory scale to industrial scale. There are various methods available to improve the solubility of the new drug in which solid dispersion emerged promising. A Solid dispersion generally composed of two components- the drug and the polymer matrix. Hence, this approach is expected to form a basis for the commercialization of many poorly water-soluble and water-insoluble drugs in their solid-dispersion formulations in the near future. This article reviews the various preparation techniques, carriers used, advantages and limitations of solid dispersions and compiles some of the recent advances. Keywords: Bioavailability, Solid Dispersion, Hydrophilic carriers, Polyethylene glycol.